DAMPAK STANDAR KECANTIKAN TERHADAP KEPERCAYAAN DIRI REMAJA DI INDONESIA: indonesia - Fifin Dwi Purwaningtyas Fifin; Futy Oktav Milenia Putri; Zumrotul Arifah (Journal of Gender Equality and Social Inclusion (gesi), 2025)
This study was motivated by the growing influence of beauty standards shaped by the media on the self-confidence of young women in Indonesia. Popular culture and beauty advertisements have constructed the notion that beauty is associated with fair skin, a slim body, and smooth facial features, which affect adolescents’ self-perception. The purpose of this study is to investigate how beauty standards affect the confidence levels of young women. This research employed a descriptive qualitative approach through in-depth interviews with two female adolescents aged 16–17 who have experienced pressure related to appearance. The findings suggest that social media plays a significant role in shaping perceptions of beauty, leading some teenagers to feel less confident if they do not meet certain physical standards. However, some participants can reject such views by realizing that beauty is relative. The study concludes that socially constructed beauty standards can negatively affect self-confidence, highlighting the importance of self-acceptance as the foundation of true beauty.